2014
DOI: 10.1007/s00270-014-1025-8
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Radiation Exposure During Endovascular Aortic Repair

Abstract: Average FO dose was a factor four higher than SO dose. Predictors for high personal doses are procedural DAP, iodinated contrast volume, and left-anterior C-arm projections greater than 60°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 25 publications
5
44
1
Order By: Relevance
“…These principles include wearing a dosimeter at all times, with cumulative doses monitored regularly and leveraged use of real-time dosimetery where possible. 44,45 Other principles include lowering the rate of fluoroscopy where applicable, minimizing the use of cinefluorography (which produces 10 times more radiation compared with standard fluoroscopy), using collimation, and maximizing the distance between the operator and x-ray source, remembering that as distance doubles exposure is reduced by a factor of 4. 46 Finally, closely monitoring the orientation and angulation of the x-ray source, particularly avoiding left anterior oblique projection, which exposes the operating team to the highest amount of scatter radiation, is key for minimizing the absorbed dose.…”
mentioning
confidence: 99%
“…These principles include wearing a dosimeter at all times, with cumulative doses monitored regularly and leveraged use of real-time dosimetery where possible. 44,45 Other principles include lowering the rate of fluoroscopy where applicable, minimizing the use of cinefluorography (which produces 10 times more radiation compared with standard fluoroscopy), using collimation, and maximizing the distance between the operator and x-ray source, remembering that as distance doubles exposure is reduced by a factor of 4. 46 Finally, closely monitoring the orientation and angulation of the x-ray source, particularly avoiding left anterior oblique projection, which exposes the operating team to the highest amount of scatter radiation, is key for minimizing the absorbed dose.…”
mentioning
confidence: 99%
“…Although the DR AK is the most reliable and is independent of the collimation for DR analysis, DAP better correlates with the operator radiation dose and the total absorbed by the patients. 13 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the current DRs were not corrected for tissue radiosensitivity, age, or sex and do not represent the actual stochastic parameter Sieverts, and both DAP and AK are direct outputs and do not include the backscatter factor. 13 However, understanding the multifactorial effect of different radiation predictors on the direct measured DR can provide an insight as to how the final cumulative radiation dose for each patient and C-arm configuration is created.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also identified that personal behavior within the fluoroscopic suite alters dose considerably. Depending on their responsibilities during the procedure nurses may have greater opportunity of deliberately increasing their distance from the patient resulting in a decrease in dose …”
Section: Methodsmentioning
confidence: 99%
“…There has been increasing concern over recent epidemiological evidence suggesting that radiation‐induced cataracts can occur at much lower doses than previously assumed . Staff involved in fluoroscopic CV procedures have demonstrated an elevated incidence of radiation‐associated lens changes . In response, in 2011 the ICRP recommended reducing the occupational dose limit for the eye from 150 mSv (millisievert) to 20 mSv per year .…”
Section: Introductionmentioning
confidence: 99%